The Effect of Service Quality, Insurance Costs, and Installment Size on Customer Satisfaction Multi-Purpose Financing: Case Study at Bank Sumut Syariah Padangsidimpuan - Afriani, Lilia; Syahriza, Rahmi; Harianto, Budi (Borong Newinera Publisher, 2024)
This research aims to analyze the influence of service quality on customer satisfaction, the influence of insurance costs on customer satisfaction and the size of installments on customer satisfaction for multi-purpose financing at the Sumut Syariah Bank, Padangsidimpuan Branch. This research uses primary data by distributing questionnaires to multi-purpose financing customers. The population of this research is all multi-purpose financing customers with a total of 862 people. The sample used in this research was 90 respondents. The validity test uses the Pearson Product Moment correlation test, while the reliability test uses Cronbach alpha. Classic assumption tests include normality tests, multicollinearity tests, heteroscedasticity tests and autocorrelation tests. Hypothesis testing in this study used multiple linear regression analysis. The research results state that service quality and insurance costs partially have a positive and significant effect on customer satisfaction. This means that the higher the quality of service provided will increase customer satisfaction, and the suitability of the insurance costs provided with the benefits obtained by the customer will provide a level of customer satisfaction. Meanwhile, the installment amount does not have a significant effect on customer satisfaction, this is because previously the installment amount had been analyzed using scoring analysis which had an influence on the installment amount.